The Nutrition Status and Learning Achievement of Mertoyudan Muhammadiyah Innovative Elementary School's Students - Dwi Sulistyono; Heni Setyowati Esti Rahayu; Robiul Fitri Masithoh (Universitas Muhammadiyah Semarang, 2020)
Nutritional problems in children are still common, including malnutrition and overweight and obesity. If this problem is not resolved it will have an impact on lack of learning achievement. This study aims to identify the nutritional status of elementary school children and their correlation with learning achievement in mathematics. This cross sectional study used a sample of 56 children in grade 1 elementary school. Nutritional status assessment is based on the Republic of Indonesia's Minister of Health Regulation No. 2 of 2020 concerning Child Anthropometry Standards. Category and threshold (Z score) nutritional status of children based on body mass index according to age (IMT / U) of children aged 5-18 years. Learning achievement is measured by the report card grades for mathematics subjects. Data analysis with Pearson product moment test and Chi-square. The results showed the nutritional status of children; thin: 6 people (10.7%), normal: 37 people (66.1%), fat: 4 people (7.1%) and obese: 9 people (16.1%). The average value of mathematics subjects is 93.16 ± 3.677. There is a relationship between nutritional status and learning achievement in mathematics (p = 0,000). Nutrition problems in children both undernutrition and over nutrition (overweight and obese) need to be addressed so that learning achievement in the future will be optimal.